· · · · 20 2018 07:43:22



FAQ







...
...
...


: 5


: 33
: tgolovko2010

@Mail.ru
#8
( , t+dt ; m dm ; v+dv ; dm (u+v)). dP = (m dm)(v dv) + (u + v)dm mv = mv +vdm + mdv dm dv + udm + vdm mv = mdv + udm. dP = mdv + udm ; dt: dP / dt = mdv / dt + udm / dt ; ma = F udm / dt ; Fp = udm / dt ( ). [m*a = F Fp] .
, F=0 ; ma = - udm / dt ;
mdv / dt = - udm / dt; mdv = - udm; dv = - udm / m ;
v = - ( m 0 m 0 m) udm / m = - u () dm / m =
= u*ln (m 0 /m 0 - m). [v = u*ln (m 0 / m0 - m)]
v , u , m .
.
.
.

, .

.






?
.

?
.

...
...
...
4.1. ...
5.6. ...
5.2. ...
...
5.16. ...
5.10. ...
5.7. ...
5.3. ...
...


...
...
2.4.1. ...
5.3. ...
...
2.4.1. ...

44
65



...
54
5.1. ...
3.3.6. .1...
5.4. ...

5.7. ...
5.7. ...
3.3.9. ...
3.6. .
5.7. ...
5.2. ...